Implementasi Sistem Manajemen Mutu ISO/IEC 17025:2017 pada Laboratorium Pengujian Produk Pertanian dengan Studi Kasus di Indonesia: Implementation of ISO/IEC 17025:2017 Quality Management System in Agricultural Product Testing Laboratories with Case Studies in Indonesia - Mela Faradika; Maria Paulina (Universitas Bengkulu, 2022)
Agricultural product testing laboratories have a strategic role in supporting the safety and quality of Indonesian agricultural products. This study examines the implementation of the ISO/IEC 17025:2017 Quality Management System (QMS) in agricultural product testing laboratories in Indonesia through a journal review approach. The results showed that the implementation of ISO/IEC 17025:2017 QMS has a significant impact on improving the quality of testing, human resource competence, stakeholder trust, and competitiveness of Indonesian agricultural products in the global market. However, there are still various obstacles in its implementation, including limited resources, complexity of documentation, and the need to increase personnel competence. Integrated policy support is needed to optimize the implementation of ISO/IEC 17025:2017 SMM in agricultural product testing laboratories in Indonesia.